Seasonality in telomerase activity in relation to cell size, DNA replication, and nutrients in the fat body of Apis mellifera - Koubová, Justina; Sábová, Michala; Brejcha, Miloslav; Kodrík, Dalibor; Čapková Frydrychová, Radmila (Scientific reports, 2021)
In honeybees (Apis mellifera), the rate of aging is modulated through social interactions and according to caste differentiation and the seasonal (winter/summer) generation of workers. Winter generation workers, which hatch at the end of summer, have remarkably extended lifespans as an adaptation to the cold season when the resources required for the growth and reproduction of colonies are limited and the bees need to maintain the colony until the next spring. In contrast, the summer bees only live for several weeks. To better understand the lifespan differences between summer and winter bees, we studied the fat bodies of honeybee workers and identified several parameters that fluctuate in a season-dependent manner. In agreement with the assumption that winter workers possess greater fat body mass, our data showed gradual increases in fat body mass, the size of the fat body cells, and Vg production as the winter season proceeded, as well as contrasting gradual decreases in these parameters in the summer season. The differences in the fat bodies between winter and summer bees are accompanied by respective increases and decreases in telomerase activity and DNA replication in the fat bodies. These data show that although the fat bodies of winter bees differ significantly from those of summer bees, these differences are not a priori set when bees hatch at the end of summer or in early autumn but instead gradually evolve over the course of the season, depending on environmental factors.
Keywords: chování zvířat; telomerasa; Adaptation, Physiological; Longevity; Fat Body; Telomerase; stárnutí; Animal Nutritional Physiological Phenomena; tukové těleso; zvířata; Aging; včely; Cell Size; DNA Replication; roční období; Bees; replikace DNA; Seasons; fyziologie výživy zvířat; dlouhověkost; fyziologická adaptace; sociální interakce; Animals; velikost buňky; Behavior, Animal; Social Interaction